Inclusive Science Communication training for first-year STEM students promotes their identity and self-efficacy as scientists and science communicators - Alderfer, Sydney; McMillan, Rachel; Murphy, Katlyn; Kelp, Nicole (Frontiers in Education, 2023)
It is critical for STEM students to be able to discuss science with diverse audiences, yet many STEM students do not receive adequate training in these skills. When students have the skills to communicate about science, they may feel a resulting sense of empowerment as a scientist as well as help members of society understand science. In this study, we developed, implemented, and evaluated a workshop that gave students understanding of and practice in applying Inclusive Science Communication. We assessed the workshop via a mixed-methods approach. We quantified student affective measures that are associated with STEM persistence, such as science self-efficacy and science identity, showing that the workshop increased these measures both for students of marginalized identities and for students who do not hold these identities. We also assessed student open-ended responses for themes related to the Theory of Planned Behavior, Community Cultural Wealth, and White Supremacy Culture, finding that forms of cultural capital empowered students to perform science communication behaviors while power imbalances, fear of conflict, and perfectionism presented barriers to these behaviors. This study highlights the importance of providing explicit training and practice in Inclusive Science Communication for undergraduate STEM students. Our results also suggest that students need the opportunity for reflexivity that is, the practice of reflecting upon their identities and motivationsin order to develop in their identity and confidence as scientists and science communicators.